PENGARUH KUALITAS LABA TERHADAP ABNORMAL AUDIT DELAY DAN DAMPAKNYA TERHADAP RELEVANSI LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Dipa Radipa; Imam Ghozali (Diponegoro Journal of Accounting, 2019)
This study discusses the improvement of earnings quality against abnormal audit delays. The independent variable in this study is earnings quality. While the dependent variable used in this study is the relevance of earnings.This study uses secondary data from reports of manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. Data collection methods use the method of merging data (unification). The total sample of this study was 160. This study uses multiple regression analysis methods for the relationship between the independent variable and the dependent variable. The results showed earnings quality had a negative and significant effect on the delay in abnormal audits and the delay in abnormal audits had a significant effect on the relevance of values but with a positive direction.